2015
DOI: 10.1371/journal.pone.0134591
|View full text |Cite|
|
Sign up to set email alerts
|

Regulatory B Cell Function Is Suppressed by Smoking and Obesity in H. pylori-Infected Subjects and Is Correlated with Elevated Risk of Gastric Cancer

Abstract: Helicobacter pylori infection occurs in more than half of the world’s population and is the main cause for gastric cancer. A series of lifestyle and nutritional factors, such as tobacco smoking and obesity, have been found to elevate the risk for cancer development. In this study, we sought to determine the immunological aspects during H. pylori infection and gastric cancer development. We found that B cells from H. pylori-infected patients presented altered composition and function compared to uninfected pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…We further demonstrated that the frequency of IL10 + B cells was also significantly lower in DM patients than in healthy controls (1.139 ± 0.156% vs 2.372 ± 0.205%, p < 0.001), which is consistent with previous reports describing a similar trend in the CD19 + CD24 high CD38 high Bregs and IL-10 + B cells of patients with other diseases 25 26 .…”
Section: Discussionsupporting
confidence: 92%
“…We further demonstrated that the frequency of IL10 + B cells was also significantly lower in DM patients than in healthy controls (1.139 ± 0.156% vs 2.372 ± 0.205%, p < 0.001), which is consistent with previous reports describing a similar trend in the CD19 + CD24 high CD38 high Bregs and IL-10 + B cells of patients with other diseases 25 26 .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, a significant inverse association of high dietary flavonols intake with a reduced risk of EC and GC was observed in smokers (OR = 0.81, 95% CI: 0.71–0.91) but not in nonsmokers (OR = 1.07, 95% CI: 0.91–1.25). Tobacco smoking can cause oxidative stress, and both oxidative stress and smoking tobacco are related to an increased risk of EC and GC [ 41 , 42 ]. The possible chemopreventive mechanism of dietary flavonols may be attributed to their anti-oxidant properties, not only direct anti-oxidant action, but more importantly the ability to modulate related enzymatic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is a contributing factor of the carcinogenesis of gastric cancer [ 31 , 35 ]. Recently it has been reported that smoking suppresses regulatory B cell and inhibits the production of interleukin 10; both events may increase the risk of gastric cancer [ 36 ]. Our results suggest that increased DUOX2 expression may contribute to the smoking-induced tumorigenesis of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%